2016
DOI: 10.1089/ten.tea.2015.0354
|View full text |Cite
|
Sign up to set email alerts
|

Porous and Nonporous Nerve Conduits: The Effects of a Hydrogel Luminal Filler With and Without a Neurite-Promoting Moiety

Abstract: Nerve conduits prefilled with hydrogels are frequently explored in an attempt to promote nerve regeneration. This study examines the interplay in vivo between the porosity of the conduit wall and the level of bioactivity of the hydrogel used to fill the conduit. Nerve regeneration in porous (P) or nonporous (NP) conduits that were filled with either collagen only or collagen enhanced with a covalently attached neurite-promoting peptide mimic of the glycan human natural killer cell antigen-1 (m-HNK) were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Despite these observations of modulated neurite growth by natural ECM hydrogel fillers, a comparison revealed that they were still outperformed by the “gold standard” autograft . Furthermore, a more recent study also indicated that the presence of natural ECM bulk hydrogel can expedite the infiltration of non‐neuronal cells into the conduit space, promoting fibrotic tissue formation and leading to impaired neural regeneration …”
Section: Isotropic Hydrogel Fillersmentioning
confidence: 99%
“…Despite these observations of modulated neurite growth by natural ECM hydrogel fillers, a comparison revealed that they were still outperformed by the “gold standard” autograft . Furthermore, a more recent study also indicated that the presence of natural ECM bulk hydrogel can expedite the infiltration of non‐neuronal cells into the conduit space, promoting fibrotic tissue formation and leading to impaired neural regeneration …”
Section: Isotropic Hydrogel Fillersmentioning
confidence: 99%
“…Braided TyrPC NGTs also offer a very high degree of kink-resistance, allowing for over 120° of flexing without luminal occlusion [9]. Earlier small animal studies have demonstrated that TyrPC NGTs significantly enhance regeneration and functional recovery, and exhibit excellent mechanical strength, suturability, and flexibility [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, braiding of polymer fibers has been introduced to generate porous NGTs with mechanical properties and flexibility suitable for nerve repair [7][8][9]. In this study, a braided NGT was fabricated using two polymers chosen from a library of tyrosine-derived polycarbonates (TyrPCs), which have previously been shown to facilitate nerve regeneration in rodent models and demonstrated improved functional recovery in small gap injuries [10][11][12]. While braiding may improve mechanical strength and increase kink-resistance, macropore structures may form allowing for tissue infiltration into the conduit that can hinder nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies have reported that NGCs filled with inner filler in lumen can serve as guidance channel to enhance axonal regeneration compared to hollow NGCs . However, another researcher has mentioned that the inner filler may only be beneficial when it is impermeable to infiltrate fibrotic tissue . Thus, we designed hollow form of NGC for guiding infiltration of host nerve tissue migration for nerve regeneration along with micropattern and permeability for the inner layer of NGC.…”
Section: Discussionmentioning
confidence: 99%
“…[32] However, another researcher has mentioned that the inner filler may only be beneficial when it is impermeable to infiltrate fibrotic tissue. [33] Thus, we designed hollow form of NGC for guiding infiltration of host nerve tissue migration for nerve regeneration along with micropattern and permeability for the inner layer of NGC.…”
Section: Discussionmentioning
confidence: 99%